2011
DOI: 10.1016/j.pt.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Do regulatory antibodies offer an alternative mechanism to explain the hygiene hypothesis?

Abstract: The 'hygiene hypothesis', or lack of microbial and parasite exposure during early life, is postulated as an explanation for the recent increase in autoimmune and allergic diseases in developed countries. The favored mechanism is that microbial and parasite-derived products interact directly with pathogen recognition receptors to subvert proinflammatory signaling via T regulatory cells, thereby inducing anti-inflammatory effects and control of autoimmune disease. Parasites, such as helminths, are considered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…The anti‐inflammatory properties of the sialylated Fc suggest that Fc‐fusion proteins lacking sialic acid (or other sugars) should make better vaccines. That glycosylation status determines the pro‐ or anti‐inflammatory ability of IgG is consistent with the observation that decreased sialylation and galactosylation of IgG are observed in patients with arthritis (Jefferis, 2009), and modifications to the carbohydrate content of IgG have been posited as a molecular explanation for the ‘hygiene‐hypothesis’ (Mekhaiel et al, 2011a). The important contribution of specific sugars is exemplified by de‐fucosylated therapeutic Abs that exhibit increased ADCC activity (Jefferis, 2009; Peipp et al, 2008; Shoji‐Hosaka et al, 2006).…”
Section: Glycosylation Of Fc‐fusion Proteins and Their Use In Ivigsupporting
confidence: 75%
“…The anti‐inflammatory properties of the sialylated Fc suggest that Fc‐fusion proteins lacking sialic acid (or other sugars) should make better vaccines. That glycosylation status determines the pro‐ or anti‐inflammatory ability of IgG is consistent with the observation that decreased sialylation and galactosylation of IgG are observed in patients with arthritis (Jefferis, 2009), and modifications to the carbohydrate content of IgG have been posited as a molecular explanation for the ‘hygiene‐hypothesis’ (Mekhaiel et al, 2011a). The important contribution of specific sugars is exemplified by de‐fucosylated therapeutic Abs that exhibit increased ADCC activity (Jefferis, 2009; Peipp et al, 2008; Shoji‐Hosaka et al, 2006).…”
Section: Glycosylation Of Fc‐fusion Proteins and Their Use In Ivigsupporting
confidence: 75%
“…The trend for a higher response to vaccination in pigs housed in poor sanitary conditions might suggest that the degradation of sanitary conditions stimulates the antigen-specific humoral response. Indeed, hypergammaglobulinemia is commonly associated with infection and it has been suggested that poor sanitary conditions could have a similar effect on immunoglobulin production (Mekhaiel et al, 2011). Thus, the ability of pigs in poor sanitary conditions to cope with pathogen exposure could be improved through continual stimulation of immune system.…”
Section: Responses Of Pigs To the Degradation Of Sanitary Conditionsmentioning
confidence: 99%
“…In helminth infections, high IgG4 : IgE ratio has been associated with reduced pathology while favouring a heavy worm load [150, 165, 166]. Interestingly, IgG4 may be one of the “regulatory antibodies” resulting from IgG syalilation involved in the control of immune disorders [167, 168]. …”
Section: Control Of Effector Responses In Atopy and Schistosome Inmentioning
confidence: 99%